2015
DOI: 10.1103/physrevb.92.045438
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of electrically excited surface plasmon polaritons by gold nanoparticles studied by optical interferometry with a scanning tunneling microscope

Abstract: We study the scattering of electrically excited surface plasmon polaritons (SPP) from individual nanostructures. The tunneling electrons from a scanning tunneling microscope (STM) are used to excite an outgoing , circular SPP wave on a thin (50-nm) gold film on which isolated gold nanoparticles (NPs) have been deposited. Interaction of the excited SPPs with the NPs leads to both in-plane (SPP-to-SPP) and out-of-plane (SPP-to-photon) scattering. We use SPP leakage radiation microscopy to monitor the interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…[14] Since then both photon and SPP emission have been reported from various macroscopic MIM tunneling devices including scanning tunneling microscope (STM), [26] molecular junctions, [27] metallic break junctions, [28] nanowire-metal stripe junctions, [29] and metal-2D material hybrid systems. [30] In the past, modulation of the spatial coherence of light by plasmonic near-field has been demonstrated in Young's interference experiments, [31,32] in metal stripe waveguides supporting SPPs [9] and also in the context of inelastic tunneling, with STM light emission, [33,34] where the localized plasmonic response of the STM tip [35] plays a crucial role. For large area TJs, [18] the lack of correlation between inelastic tunneling events typically results in spatially incoherent and spectrally broad (lack of temporal coherence) photon or plasmon emission.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Since then both photon and SPP emission have been reported from various macroscopic MIM tunneling devices including scanning tunneling microscope (STM), [26] molecular junctions, [27] metallic break junctions, [28] nanowire-metal stripe junctions, [29] and metal-2D material hybrid systems. [30] In the past, modulation of the spatial coherence of light by plasmonic near-field has been demonstrated in Young's interference experiments, [31,32] in metal stripe waveguides supporting SPPs [9] and also in the context of inelastic tunneling, with STM light emission, [33,34] where the localized plasmonic response of the STM tip [35] plays a crucial role. For large area TJs, [18] the lack of correlation between inelastic tunneling events typically results in spatially incoherent and spectrally broad (lack of temporal coherence) photon or plasmon emission.…”
Section: Introductionmentioning
confidence: 99%
“…Combining our technique with polarimetry would lead to the characterization of the optical response of chiral nano and microstructures [70]. Beyond optical mode characterization, our technique may be used as an interferometric tool to determine the phase in the optical response of nanostructures, as introduced in [42]. It is also a valuable tool for the testing and design of integrated plasmonic microstructures in view of their integration in optoelectronic microdevices, as proposed in [44].…”
Section: Resultsmentioning
confidence: 99%
“…Over the last decade, the combination of ambient STM with optical microscopy has been increasingly applied to experiments in nano-optics [28][29][30][31][33][34][35][36][37][38][39][40][41][42][43][44][45]. Most recently, this technique has been used to study the propagation of surface plasmon polaritons (SPPs) in 2D plasmonic crystals [43] and the spectral response of plasmonic lenses [44]; however, the measurement of the dispersion relation of the optical modes in a plasmonic system using this technique has never been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was found that the gap mode can also excite the surface plasmon polaritons (SPPs) propagating along the metal surface 31,32 . This provides an efficient, local, electrical way of launching SPPs in optical structures, and its applications received considerable attention recently [33][34][35][36][37][38] . These results suggest that the electrical excited gap plasmon modes have several optical decay channels.…”
Section: Introductionmentioning
confidence: 99%